(untitled) (The Review of Diabetic Studies, 2021)
OBJECTIVE: The aim of this study was to evaluate the dietary habits and irrational beliefs of apparently healthy individuals in relation to their 10-year diabetes incidence. METHODS: The ATTICA study (2002-2012) is a prospective populationbased cohort study, in which 853 participants (453 men (aged 45 ± 13 years) and 400 women (aged 44 ± 18 years)) without a history of cardiovascular disease (CVD) underwent psychological evaluations. Among other things, participants completed the Irrational Beliefs Inventory (IBI, range 0-88), a brief, self-reported measure consistent with the Ellis model of psychological disturbance. Demographic characteristics, detailed medical history, and dietary and other lifestyle habits were evaluated as well. Diagnosis of diabetes at follow-up examination was based on the criteria of the American Diabetes Association. RESULTS: Mean IBI score was 53 ± 10 in men and 51 ± 11 in women (p = 0.68). IBI was positively associated with the 10-year type 2 diabetes incidence (hazard ratio: 1.14; 95% CI: 1.04-1.25) in both men and women, and even more distinctly associated with participants with the following characteristics: lower education status, married, overweight, smokers, anxiety and depressive symptomatology, and unhealthy dietary habits. Especially, participants with increased irrational beliefs and low adherence to the Mediterranean diet were 37% more likely to develop type 2 diabetes than those with the reverse status (hazard ratio: 3.70; 95% CI: 2.32-5.88). CONCLUSIONS: These data support the need for lifestyle changes towards healthier nutrition which can be achieved by educating people so that they are equipped to recognize false and unhelpful thoughts and thus to prevent negative psychological and clinical outcomes such as mental health disorders and type 2 diabetes.